The nature of music education at the South African College of Music : an interpretative enquiry - Montocchio, Edouard Francis (School of Education, 2016)
This project began with a Preliminary Study, in which the members of the 1985 final-year class at the SACM were interviewed to investigate their goals and the way in which these goals related to their curricula. The main findings of this study were that the students were unclear about their goals, their reasons for studying music at the SACM, and their future prospects. In addition, their perception of the SACM included criticism of items of curricular content and teaching methods. These findings led to a central goal question which was to become the focus of a more objective, broadly based, interpretative study that would be more apposite for investigating a topic of this complexity. This goal question is: "WHAT ISSUES DO THE PEOPLE INVOLVED AT THE SACM PERCEIVE AS AREAS OF CONCERN, IN RESPECT OF THEIR EXPERIENCE AT THE SACM, AND WHAT ARE THESE CONCERNS?" Accordingly, the main part of this investigation took the form of an attempt to sketch a collective perception of the nature of the education provided at the SACM. An institution like this is the theatre of numerous simultaneous agendas and interpretations. Its activities, directions and the education which it provides will appear different trom different perspectives. It was thus decided to obtain responses from a range of people connected with the SACM, to reflect these different perspectives. The sample who contributed to this perception is drawn from among the teachers, administrators, students, past students, parents of students and others professionally connected with the SACM.